2008
DOI: 10.1111/j.1467-8527.2007.00391.x
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Purpose of Learning Science? An Analysis of Policy and Practice in the Primary School

Abstract: The paper explores the current rationale for primary science in England with a focus on how competing perspectives arising from perceptions of educational ideology and policy discourse have helped to shape current practice. The aim will be to provide a conceptual understanding of this by focusing specifically on how policy has influenced practice. In particular it will consider the way in which discourse and policy text have contributed to the emergent rationale for primary science which in many ways reflects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Their skills contribute to the advancement of technology and its impact on various industries and sectors. These findings support previous study that pointed out the purpose of learning science (Eady, 2008).…”
Section: Categories Of Purpose-based Careerssupporting
confidence: 93%
“…Their skills contribute to the advancement of technology and its impact on various industries and sectors. These findings support previous study that pointed out the purpose of learning science (Eady, 2008).…”
Section: Categories Of Purpose-based Careerssupporting
confidence: 93%
“…A key challenge for primary science is to secure sufficient weekly curriculum time, making manageability of assessment processes a key priority in the current climate. Eady's (2008) study of the purpose of teaching science in primary school found that many teachers saw scientific knowledge as paramount for performance in end of Key Stage testing. If teachers saw a strong relationship between the purpose of primary science and the passing of tests, the removal of those tests in 2009 could be one of the reasons for the reduced status of primary science.…”
Section: Status Of Primary Science In Englandmentioning
confidence: 99%
“…In contrast, Stobart (2009) suggests that a narrow focus on outcomes and tests is counter-productive because whilst it appears to raise the status of science, it is at the expense of a broader curriculum and deeper learning (p176). Eady (2008) also suggested that the commonly used QCA schemes of work (DfEE/QCA 1998) provided a progression of pre-planned lessons that negated the need to elicit pupil ideas; with a change in National Curriculum (DfE 2013a) these QCA schemes also became obsolete.…”
Section: Status Of Primary Science In Englandmentioning
confidence: 99%